Recent updates on ions and nutrients uptake by halotolerant freshwater and marine microalgae in conditions of high salinity. (December 2021) - Zafar, Abdul Mannan; Javed, Muhammad Asad; Aly Hassan, Ashraf; Mehmood, Khalid; Sahle-Demessie, Endalkachew
Abstract: Algae is an appropriate natural resource to augment the optimal use of undesired ions in water and wastewater. Increasing algal cells, the consumption of particular ions, including chloride, nitrate, phosphate, and ammonium, provides a suitable way to optimize water treatment processes. Different algal species have the capability to survive in extreme salinities by developing resistance against osmotic pressure in saline water. The current study reviews the effect of salinity on algal biomass production, algal growth rate, chlorides, nitrates, phosphates, chemical oxygen demand (COD), total nitrogen, total phosphorus, and ammonium ions. Mainly algae cultivated in freshwater, synthetic brackish water, seawater, and hypersaline water, were studied for this review. Various ion uptake mechanisms used by the algal cell are summarized, focusing on biosorption and bioaccumulation processes. Critical parameters such as light intensity, pH, and temperature variations significantly influence ion and nutrients uptake efficiencies. Analysis performed on collected data indicated that halophytic algae could survive in high salinities at elevated growth rates compared to freshwater. The halotolerant algal species showed an inclining trend of chloride ion removal with an elimination capacity of 7.5 g.m −3 .h −1 . Moreover, the nitrate uptake rate in halophytic algae is 10-folds higher to phosphate, regardless of salinity level. It could be concluded that microalgae will be beneficial for ion and nutrient uptake processes in treating high saline water. Graphical abstract: Unlabelled Image Highlights: Algae uptakes ions for growth even at high salinity levels. Biomass growth and ion elimination capacity decreased with increasing salinity. Optimization of pH, temperature, and light intensity affects algal growth positively. Ion uptake happens through biosorption (fast) and bioaccumulation (slow) process. Water treatment using algae is an environmental and sustainable approach.